Effectiveness of Visual Basic for Application based PowerPoint as an Interactive Learning Media to Increase Learning Interest in Astronomy - Abu Yazid Raisal; Muhammad Hidayat; Nurul Zahriani Jf; Rihan Yuhyi (Universitas Sebelas Maret, 2025)
This study aims to investigate the effectiveness of VBA-based PowerPoint as an interactive learning medium to increase interest in learning astronomy. The research design used was a Pre-Experimental Design with a one-group pretest-posttest design. The subjects of this study were 20 second-semester students majoring in Astronomy at the University of Muhammadiyah Sumatera Utara. Research data were collected using a questionnaire designed with a Likert scale. The questionnaire consisted of 18 statements, comprising both positive and negative statements. The data analysis technique used was the Paired Sample T-Test. The results of the study indicated that interactive learning media, based on PowerPoint and utilizing VBA, can increase students' interest in learning basic astronomy. The results of the Paired Sample T-Test showed that the significance value (2-tailed) obtained was 0.000. This result indicates a significant difference in learning interest before and after using the interactive PowerPoint-based VBA learning media. This suggests that the use of interactive PowerPoint-based VBA learning media is effective in enhancing learning interest in basic astronomy education. This finding implies that teachers can adopt PowerPoint enhanced with VBA as a cost-effective and easily accessible tool to stimulate learning interest in complex subjects